2011
DOI: 10.1103/physrevlett.107.108102
|View full text |Cite
|
Sign up to set email alerts
|

Underwound DNA under Tension: Structure, Elasticity, and Sequence-Dependent Behaviors

Abstract: DNA melting under torsion plays an important role in a wide variety of cellular processes. In the present Letter, we have investigated DNA melting at the single-molecule level using an angular optical trap. By directly measuring force, extension, torque, and angle of DNA, we determined the structural and elastic parameters of torsionally melted DNA. Our data reveal that under moderate forces, the melted DNA assumes a left-handed structure as opposed to an open bubble conformation and is highly torsionally comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
170
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(201 citation statements)
references
References 35 publications
(57 reference statements)
28
170
3
Order By: Relevance
“…2 B, we present measurements of L e as a function of F for different fixed values of n t between n t ¼ 0 and n t ¼ À400 from left to right. These measurements were taken for bare DNA under physiological conditions, and similar measurements have been reported several times in the past (29,39,52,53). These data illustrate the effects on DNA extension of imposing turns (denaturation or plectoneme formation) or applying forces to the bead.…”
Section: Single-molecule Mt Measurementssupporting
confidence: 77%
“…2 B, we present measurements of L e as a function of F for different fixed values of n t between n t ¼ 0 and n t ¼ À400 from left to right. These measurements were taken for bare DNA under physiological conditions, and similar measurements have been reported several times in the past (29,39,52,53). These data illustrate the effects on DNA extension of imposing turns (denaturation or plectoneme formation) or applying forces to the bead.…”
Section: Single-molecule Mt Measurementssupporting
confidence: 77%
“…A recent single-molecule mechanics study on torsionally induced melting of DNA observed the onset of melting in DNA held under large tension (up to 36 pN) at linking deficits near s z À0.05. Complete conversion of B-DNA to L-DNA is not observed until s z À1.6 (66). Similarly, in two other recent single-molecule experiments, at tensions where no plectoneme formation occurs (R1 pN), the onset of DNA melting was not observed until s z À0.02 (26,40).…”
Section: Possible Implications For Transcriptional Control Of Chromosmentioning
confidence: 54%
“…It is true that single-molecule mechanics studies demonstrate the formation of noncanonical secondary transitions when DNA is highly underwound (24,26,66). However, these experiments involve holding the DNA molecule under tension, where writhe fluctuations are strongly suppressed compared to DNA rings in free solution.…”
Section: Possible Implications For Transcriptional Control Of Chromosmentioning
confidence: 99%
“…1, blue). Tension changes the partitioning of the negative twist between negative writhe and left-handed helices such that the slope of the extension versus twist curve for unwound DNA decreases and eventually flattens at high tension or even increases gradually as the DNA is unwound (Sheinin et al 2011) (Fig. 1, red).…”
Section: Dna Under Torsion Twists and Then Supercoilsmentioning
confidence: 99%
“…This asymmetry reflects the chirality of the double helix and is due to conformational changes in unwound DNA under tension (Leger et al 1999;Marko and Neukirch 2013). After extensive unwinding that converts the entire molecule to a left-handed form, the extension finally shrinks again as left-handed plectonemes form in left-handed DNA (Sheinin et al 2011).…”
Section: Dna Under Torsion Twists and Then Supercoilsmentioning
confidence: 99%